2015
DOI: 10.3390/su71114785
|View full text |Cite
|
Sign up to set email alerts
|

Intermediary Propositions for Green Growth with Sustainable Governance

Abstract: Abstract:This article gives an overview of the conceptual characteristics of sustainable development by searching the governance-oriented intermediaries. It shows how the new paradigm of green growth evolved through international consensus and how this paradigm of the public-private partnership (PPP) could work with the new propositions of intermediation. The historical context in the latter half of the 20th century is outlined, in which a paradigm shift toward PPP was caused by green growth policies. It empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…However, technological advancement itself is not sufficient to solve modern environmental problems such as natural resource depletions and global climate change [2]. These problems, which are embedded in a combination of complex social-ecological systems with multiple subsystems and internal variables within these subsystems, demand collaborative governance where resource users participate in developing rules and norms for managing the resources [2,3]. Policy solutions with one-size-fit-all recommendations are likely to fail to achieve environmental sustainability without voluntary and cooperative participation from the public.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, technological advancement itself is not sufficient to solve modern environmental problems such as natural resource depletions and global climate change [2]. These problems, which are embedded in a combination of complex social-ecological systems with multiple subsystems and internal variables within these subsystems, demand collaborative governance where resource users participate in developing rules and norms for managing the resources [2,3]. Policy solutions with one-size-fit-all recommendations are likely to fail to achieve environmental sustainability without voluntary and cooperative participation from the public.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this instrumental mentality has been equally applied to the method of dealing with environmental problems that threaten our future survival. However, technological advancement itself is not sufficient to solve modern environmental problems such as natural resource depletions and global climate change [2]. These problems, which are embedded in a combination of complex social-ecological systems with multiple subsystems and internal variables within these subsystems, demand collaborative governance where resource users participate in developing rules and norms for managing the resources [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This paper showed clearly the lack of governance for a sustainable ETS policy in Korea; thus, the Korean government should engage in greater proactive efforts to upgrade the future sustainable performance of the ETS [37]. Especially, for the sustainable performance of ETS, the covered companies should make efforts to invest in green technology to improve its environmental efficiency, and the paper showed that there is huge potential for benefits from green investment to enhance environmental efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with these undesirable outcomes, all of the governments in the region have shifted their policy paradigms to place much more emphasis on environmental issues [1]. Due to the ever-increasing complexity of the issues in this field of sustainable development or green growth, there were many diverse views and suggestions put forward in SAC 2016, with most of them focused on matters of governance or the determining factors of various governance mechanisms.…”
Section: Background Of the Special Issuementioning
confidence: 99%